2020
DOI: 10.1101/2020.02.22.20026500
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Neurological Manifestations of Hospitalized Patients with COVID-19 in Wuhan, China: a retrospective case series study

Abstract: OBJECTIVETo study the neurological manifestations of patients with coronavirus disease 2019 . DESIGN Retrospective case series SETTINGThree designated COVID-19 care hospitals PARTICIPANTSTwo hundred fourteen hospitalized patients with laboratory confirmed diagnosis of severe acute respiratory syndrome from coronavirus 2 (SARS-CoV-2) infection. Data were collected from 16 January 2020 to 19 February 2020. MAIN OUTCOME MEASURESClinical data were extracted from electronic medical records and reviewed by a trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

37
879
9
86

Year Published

2020
2020
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 746 publications
(1,028 citation statements)
references
References 12 publications
37
879
9
86
Order By: Relevance
“…There are already some evidences that COVID-19 can cause damage to tissues and organs other than the lung. In a study of 214 COVID-19 patients, 78 (36.4%) patients had neurological manifestations [32]. In addition, there is already evidence of ocular surface infection in patients with COVID-19, and SARS-CoV-2 RNA was detected in eye secretions of patient [33].…”
Section: Clinical Characteristics Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…There are already some evidences that COVID-19 can cause damage to tissues and organs other than the lung. In a study of 214 COVID-19 patients, 78 (36.4%) patients had neurological manifestations [32]. In addition, there is already evidence of ocular surface infection in patients with COVID-19, and SARS-CoV-2 RNA was detected in eye secretions of patient [33].…”
Section: Clinical Characteristics Of Sars-cov-2 Infectionmentioning
confidence: 99%
“…It is therefore likely that anosmia and dysgeusia might be observed in patients with COVID-19 (Giacomelli et al, 2020;Ryan, 2020;Hopkins and Kumar, 2020). In fact, some even develop COVID-19-related symptoms only after showing neurologic symptoms (Mao et al, 2020). Recently, Beijing Ditan Hospital reported for the first time a case of viral encephalitis caused by the novel CoV attacking the CNS.…”
Section: Sars-cov-2mentioning
confidence: 99%
“…Patients with COVID-19 often suffer from severe hypoxia and viremia , which has the potential to cause toxic encephalopathy. Moreover, almost 40% of patients with COVID-19 develop headache, disturbed consciousness, and other brain dysfunction symptoms (Mao et al, 2020), and that an autopsy study reported that edema has been detected in brain tissue of COVID-19 patients . Collectively, these findings provide the evidence that COVID-19 could cause infectious toxic encephalopathy, although detailed studies are greatly required.…”
Section: Infectious Toxic Encephalopathymentioning
confidence: 99%
See 1 more Smart Citation
“…The evidence of acute neuropsychiatric symptoms in COVID-19 cases is emerging. An initial report of 217 hospitalized patients in Wuhan, China, described neurologic manifestations in nearly half of those with severe infection (40 of 88), including cerebrovascular complications (e.g., stroke), encephalopathies, and muscle injuries (Mao et al, 2020). Interestingly, total blood lymphocyte counts were significantly lower in patients with CNS-associated (e.g.…”
Section: Acute Neuropsychiatric Symptoms Associated With Sars-cov-2 Imentioning
confidence: 99%